2019
DOI: 10.1001/jamanetworkopen.2019.9826
|View full text |Cite
|
Sign up to set email alerts
|

Association of Plasma Amylin Concentration With Alzheimer Disease and Brain Structure in Older Adults

Abstract: This cohort study uses data from second-generation participants in the Framingham Heart Study to analyze the association of plasma amylin concentration with Alzheimer disease risk and brain structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 42 publications
0
19
0
Order By: Relevance
“…It has been reported that injection of the pancreatic peptide amylin potently reduces behavioral impairment and brain amyloid pathology in murine AD models 26 and proposed that amylin protects against AD effects in humans. 27 If amylin lowers Aβ pathology, we then should expect that genetically suppressed amylin gene in APP/PS1 rats will exacerbate AD pathology and behavior deficits, whereas overexpressing amylin will slow disease progression. Our results demonstrated the opposite and are consistent with data showing that intracerebroventricular human amylin administration in murine AD models promotes robust amylin-Aβ cross-seeding, accelerating AD pathology; 28 and pancreatic expression of amyloidforming human amylin in murine AD mice exacerbate cerebral amyloid burden through cumulative diabetogenic effects of the coexpressed human amylin and Aβ.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that injection of the pancreatic peptide amylin potently reduces behavioral impairment and brain amyloid pathology in murine AD models 26 and proposed that amylin protects against AD effects in humans. 27 If amylin lowers Aβ pathology, we then should expect that genetically suppressed amylin gene in APP/PS1 rats will exacerbate AD pathology and behavior deficits, whereas overexpressing amylin will slow disease progression. Our results demonstrated the opposite and are consistent with data showing that intracerebroventricular human amylin administration in murine AD models promotes robust amylin-Aβ cross-seeding, accelerating AD pathology; 28 and pancreatic expression of amyloidforming human amylin in murine AD mice exacerbate cerebral amyloid burden through cumulative diabetogenic effects of the coexpressed human amylin and Aβ.…”
Section: Discussionmentioning
confidence: 99%
“…These results directly address the potential for modulation of circulating amylin as a means to alter AD pathology. It has been reported that injection of the pancreatic peptide amylin potently reduces behavioral impairment and brain amyloid pathology in murine AD models 26 and proposed that amylin protects against AD effects in humans 27 . If amylin lowers Aβ pathology, we then should expect that genetically suppressed amylin gene in APP/PS1 rats will exacerbate AD pathology and behavior deficits, whereas overexpressing amylin will slow disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…However, amylin can aggregate when concentrations are high and become neurotoxic in cell cultures and is associated with brain amyloid burden and cognitive impairment in AD [38,39]. Recent studies have also indicated that the high plasma levels of IAPP is a pathological hallmark of insulin resistance [40] and correlates with AD diagnosis and brain structure [41]. In vitro studies revealed that curcumin significantly reduces h-IAPP fibril formation and aggregates formed in the presence of curcumin display alternative structure compared to the actual peptide [42].…”
Section: Discussionmentioning
confidence: 99%
“…Amylin amyloid deposition in the pancreas is a well-recognized hallmark feature of T2D. ,, Recently, amylin amyloid deposition was also found in the brains of T2D patients with dementia or Alzheimer’s disease, as well as in the brains of diabetic HIP animal models, raising the possibility that amylin amyloid may be a new amyloid in the brain. ,,,, The exact mechanism of such diabetes-induced neurodegeneration remains elusive. However, validating this new hypothesis will be highly significant, as it opens a new field by identifying a specific molecular link between diabetes and neurodegeneration.…”
Section: Discussionmentioning
confidence: 99%